Confluent Hypergeometric Function and Its Nexus to Different Special Functions - Tripathi, Bhadra Raj; Adhikari , Iswarmani; Regmi, Rajendra Prasad; Tripathi, Sameer (AMC Journal (Dhangadhi), 2026)
This paper aims to explore the unifying role of the Confluent Hypergeometric Function in the derivation of some special functions: Incomplete Gamma Function, Error Function, Laguerre Polynomial Function, Hermite Polynomial Function, Bessel Function, and Whittaker Function through series expansions. This study is based on a systematic review of the literature to lay out a cohesive perspective that enhances understanding of the theoretical concepts of special functions and furnishes a streamlined approach for applications across mathematics, engineering, probability, and other areas of applied mathematics.